Ribosome-dependent conversion of polyA-containing heterogenous nuclear RNA into smaller RNA molecules. - Grozdanovic, J (1975)
The polyA-containing heterogenous nuclear RNA fraction separated from total rat liver nRNA by gel filtration on Sepharose 4B followed by affinity chromatography on polyU-Sepharose and containing predominantly the 45S components becomes enzymatically bound to homologous 80S ribosomes and polyribosomes at 0 degree C. If 80S ribosomes or polyribosomes with bound poly-a-containing HnRNA are subjected to a further incubation at 37 degree C, the original 45S RNA is gradually converted into smaller RNA species of 10- 35S which remain bound to the particle. This ribosome-dependent cleavage of larger HnRNA species into smaller RNA molecules may represent the ultimate step of mRNA maturation.